A Giant Mesentric Lipoblastoma in a Two-Year Girl: A Case Report - Palit, Paritosh Kumar; Chakroborty, Abhi Kumar; Saha, Nirupama; Md Shamsuzzaman, -; Hasan, Khandoker Moynul; Sarker, Rajib Dey; Mamun, Abdullah Al; Sultana, Sarmin (Journal of Shaheed Suhrawardy Medical College, 2021)
Back ground: Abdominal lipoblastomas which are benign but uncommon soft tissue tumors in children rarely arise from the mesentery.However, benign, these may attain in large size and cause compression symptoms. Complete resection and close post-operative monitoring are necessary for avoidance of recurrence. Histopathology with immunohistochemistry in conjunction with the morphology is the gold standard for diagnosis. Herein such a rare a case of mesenteric lipoblastoma with huge abdominal distention is reported. Case presentation: A 2-year-old girl presented with an enormous abdominal swelling occupying almost all quadrants of the abdomen with repeated dull abdominal pain. The swelling was a non-tender and tensely cystic. USG and CT Scan could not distinguish the proper origin or location of the mass but demonstrated as a large encapsulated and lobulated fatty mass measuring about (16.4x10.0x18.6cm) involving right hypochondriac, epigastric, bilateral ilio-lumber, umbilical & hypogastric regions, pushing the bowel loops upward & laterally with mild mesenteric thickening of perilesional mesentery and separated from the liver & both kidneys and other intraabdominal organs. After exploratory laparotomy there revealed a well capsuled large (about 15x11x14cm)soft yellow mass displacing the entire intra-abdominal contents, connected by a single vascular pedicle with the mesentery and loosely enclosing the mesentery as a whole. Histology and immunohistochemistry of completely resected mass conûrmed the presence of mature adipocytes and immuno-morphology was compatible with Lipoblastoma. Conclusion: This case represents one of the largest mesenteric lipoblastomas in accordance to the patient’s age that histologically, mostly composed of mature adipocytes with few lipoblasts. J Shaheed Suhrawardy Med Coll, December 2020, Vol.12(1); 54-57